Rede de Reabilitação do SUS de Belo Horizonte: visão dos profissionais de saúde sobre a gestão do trabalho para a prestação do serviço - Amanda Neves Cruz Coelho (2024)
Global health trends indicate the need for expanding rehabilitation services due to the increasing demand from people with functional difficulties. In Brazil, access to rehabilitation became universal with the creation of the Sistema Único de Saúde (SUS) through the services offered in a network at its three levels of health care: Primary Care, Medium Complexity, and High Complexity. Despite the progress over the years, studies show that networked care still presents weaknesses and challenges in coordination. Considering that the effectiveness of a Health Care Network is intrinsically linked to how professionals understand the dynamics of the services, the objective of this study was to understand the Rehabilitation Network of SMSA-BH and its organizational aspects from the perspectives and concepts of the professionals working within it. This is an exploratory study using a qualitative methodology, defined as a case study. Online interviews were conducted with 33 managers and professionals involved in rehabilitation across the three levels of care, using a semi-structured interview guide. The results were analyzed through content analysis proposed by Bardin, and five categories were developed: The Rehabilitation Network: Connecting Nodes; The Work Process: Intertwining Threads; Information Sharing: Bringing Nodes Closer; Strategies and Innovation: Strengthening Threads; and Normative Bases: Efforts for Convergent Configurations. The study revealed that participants have adequate theoretical recognition of the components of this Network, but it is the operational difficulties that impact the work process, causing weaknesses in the services. The main challenges identified, in line with the literature, were high workload, reduced working hours, high staff turnover, and insufficient rehabilitation services. Additional difficulties, less explored in the literature, involve divergences in the work process between services, distance between coordinations, and lack of integration between the Network's own services and contracted or convened services. Among the factors driving the work, teamwork, the quality of human resources and interpersonal relationships, availability for coordination, and managerial support were mentioned. The primary difficulty in operationalizing the Network lies in communication. Participants expressed a desire for shared management through greater engagement with contracted and convened services and more dialogical participation in rehabilitation forums, as well as in the development of guiding documents for service practices. The need for improving the work process was also addressed, particularly through better organization of information. Actions such as Continuing Education, changes in forum formats, and strategies for information sharing by coordinations (e.g., sending emails) were suggested by participants to enhance network integration. It is hoped that the technical report intended for PBH, a technical product of this study, will serve as a valuable evaluative tool for the service and contribute to the management and organization of network work in the municipality.